Molecular typing, serotyping and cytotoxicity testing of Campylobacter jejuni strains isolated from commercial broilers in Puerto Rico - Oyarzabal, O. A.; Backert, Steffen; Williams, L. L.; Lastovica, A. J.; Miller, R. S.; Pierce, S. J.; Vieira, S. L.; Rebollo-Carrato, F. (Journal of Applied Microbiology, 2008)
Aims: Thirty Campylobacter jejuni strains isolated from fecal samples (n = 94; 32%) from 13 positive farms (n = 17; 76%) from commercial broiler chickens in Puerto Rico were analysed by molecular methods. Methods and Results: Isolates were identified with multiplex polymerase chain reaction assays, tested for their antimicrobial susceptibility and characterized with pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), serotyping and bacterial cytotoxicity in mammalian cells. Isolates exhibited high resistance to vancomycin (minimum inhibitory concentration, MIC of >256 μg ml -1) and trimethoprim (MIC of >32 μg ml-1); few were resistant to clindamycin (MIC90 4 μg ml-1), erythromycin (MIC90 8 μg ml-1) and tetracycline (MIC90 8 μg ml-1); but none was resistant to azithromycin (MIC90 4 μg ml-1), ciprofloxacin (MIC 90 1 μg ml-1) or gentamycin (MIC90 4 μg ml-1). Most strains restricted with SmaI, but a combination of SmaI-KpnI digestion was more discriminatory. MLST analysis yielded four sequence types (ST), and ST-2624 was the predominant one. Phylogenetic analysis revealed a high degree of recombination for glnA and pgm genes. The predominant serotypes were O:3 and O:5. Most strains had lowest cytotoxicity potential with Caco-2 cells, medium cytotoxicity with INT-407 and Hep-2 cells and high cytotoxicity with CHO cells. Conclusion: A low degree of antimicrobial resistance, 13 PFGE profiles, 4 ST and a large variability in cytotoxicity assays were found for these strains. Significance and Impact of the Study: This is the first characterization of C. jejuni strains isolated from broilers in Puerto Rico. The genetic diversity of these strains suggests that several techniques are needed for strain characterization. © 2008 The Authors.
Created from Fastlane, Scopus look-up
Keywords: Broiler; Campylobacter; Chicken; Cytotoxicity assays; MLST; PFGE; Serotyping